2017
DOI: 10.15376/biores.12.1.1246-1262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bamboo-Based Activated Carbons with Super-High Specific Surface Area for Hydrogen Storage

Abstract: Activated carbons (ACs) were developed from the agricultural by-products of moso bamboo by pyrolysis carbonization and the KOH activation process. N2 adsorption-desorption at 77 K, thermogravimetric analysis (TG), X-ray photoelectron spectrometry (XPS), element analysis (EA), Xray diffraction (XRD), scanning electron microscopy (SEM), highresolution transmission electron microscopy (HRTEM), and Fourier transform infrared spectroscopy (FTIR) were used to investigate the synthesis process, the impact of the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 25 publications
2
11
0
9
Order By: Relevance
“…We found that the maximum capacity reaches 1.86 wt% (77 K, 847 mmHg) for H 2 , and 3.44 mmol/g (298 K, 847 mmHg) for CO 2 . These results surpassed the capacity of the previously commercialized porous activated carbon (PAC, 1.23 wt% at 1 bar/77 K for H 2 , and 2.1 wt% at 313 K for CO 2 ) [17,29], but their capacity is lower than the results observed for chemically activated bamboo species in previous studies (2.74 wt% at 1 bar/77 K for H 2 , and 4.5 mmol/g at 1 bar/298 K for CO 2 ) [56,57]. However, we focused on finding other factors for enhancing the storage capacity.…”
Section: Surface Structure and Gas Adsorption Using Bet Analysismentioning
confidence: 61%
“…We found that the maximum capacity reaches 1.86 wt% (77 K, 847 mmHg) for H 2 , and 3.44 mmol/g (298 K, 847 mmHg) for CO 2 . These results surpassed the capacity of the previously commercialized porous activated carbon (PAC, 1.23 wt% at 1 bar/77 K for H 2 , and 2.1 wt% at 313 K for CO 2 ) [17,29], but their capacity is lower than the results observed for chemically activated bamboo species in previous studies (2.74 wt% at 1 bar/77 K for H 2 , and 4.5 mmol/g at 1 bar/298 K for CO 2 ) [56,57]. However, we focused on finding other factors for enhancing the storage capacity.…”
Section: Surface Structure and Gas Adsorption Using Bet Analysismentioning
confidence: 61%
“…With an exceptionally large surface area, a microporous nature and the possibility of an economic and scalable production, ACs are excellent candidates in efficient hydrogen storage systems [58,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. One of the most important advantages of ACs is that they can be produced from a wide variety of low-cost and renewable raw materials, such as agricultural waste or lignocellulosic materials in general, which is an important advantage compared to other carbon materials [104].…”
Section: Activated Carbonsmentioning
confidence: 99%
“…The A BET of the as-produced ACs was around 3220 m 2 g −1 . An absolute uptake, equal to 6.6 wt.% at 77 K and 4 MPa, was achieved by Zhao et al [92] using ACs produced by chemical activation of bamboo-based precursors having an A BET of 3208 m 2 g −1 . Blankenship II et al [99] obtained an excess of hydrogen uptake of 7.0 wt.% at 77 K and 2 MPa, which is one of the highest results ever reported for any carbon material.…”
Section: Activated Carbonsmentioning
confidence: 99%
“…The high cellulose content is an important point to choose the bagasse for raw material carbon production [8][9][10] . Carbon-based materials are functional for many purposes such as for gas adsorption 11,12) , wastewater treatment 13) , electrodes in media storage 14,15) , antibacterial agent 16) , gas storage 17) , and for photocatalytic uses 18) . The effort to change bagasse as a sugarcane factory waste into activated carbon is important to increase the economic value of bagasse along with its solution to waste management regarding environmental issues.…”
Section: Introductionmentioning
confidence: 99%